The radiographic evaluation of repaired canine ilial fractures (69 cases) - Breshears, L. A.; Fitch, R. B.; Wallace, L. J.; Wells, C. S.; Swiderski, J. K. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
A retrospective radiographic evaluation of 69 canine ilial fractures was performed. The patient information, concurrent injuries, fracture description, implant characteristics, fixation, radiographic outcome, and complications were assessed. Ilial fracture repairs were divided into four groups: lateral plate only, lateral plate with ventral interfragmentary screws, lateral plate with ventral plate, and ventral plate only fixation. The number of screws, degree of purchase, use of oversized screws, presence of sacral penetration, alignment, apposition, and pelvic collapse were evaluated. Radiographic follow-up (> 4 weeks) was available in 42 of these cases. Radiographic complications were recognized in 24% of the cases. All implant complications were identified within the lateral component of the fixation, but not necessarily confined to the patients repaired with only a lateral plate. Repairs that utilized ventral fixation had significantly greater screw purchase while providing additional lag screw compression across the fracture site. Of the three groups utilizing ventral stabilization (25 repairs), only one case had implant loosening. Ventral screw fixation appears to provide additional rigidity to ilial fracture repair that may be beneficial in some cases. This report describes additional surgical repair options available for repair of canine ilial fractures.
Keywords: Ilium; iliac; ilial; pelvic fracture; bone plates; lag screw; interfragmentary compression